The mTOR kinase as a target for anti-cancer drugs - Sabatini, David (Henry Stewart Talks, 2010)
Introduction to growth control, Cell size changes in normal physiology, Dual growth signals in multicellular organisms, Rapamycin and its uses, Discovery and function of mTOR growth pathways, raptor and GL, The mTOR Complex 1 (mTORC1) pathway, mTOR exists in two distinct protein complexes: mTORC1 and mTORC2, The role of the mTOR pathway in cancer